How to write anything : a complete guide - Brown, Laura (Laura Marie) (New York : W.W. Norton & Company, 2014)
Provides a common-sense approach on how to write anything, from college applications to baby announcements, and includes information on how to appropriately craft a message, choose the right words, and the select the most appropriate medium.
The writing process. You can write anything ; Finding your process -- E-writing and the technology revolution. Choose your weapon ; The process of e-writing -- The entries. Writing in your personal life ; Writing at school ; Writing at work.
Includes index.
Includes bibliographical references and index.
Keywords: English language -- Rhetoric; Report writing